Functional and Structural Integrity of Frontoparietal Connectivity in Traumatic and Anoxic Coma. Issue 8 (August 2020) - Peran, Patrice; Malagurski, Briguitta; Nemmi, Federico; Sarton, Benjamine; Vinour, Hélène; Ferre, Fabrice; Bounes, Fanny; Rousset, David; Mrozeck, Segolène; Seguin, Thierry; Riu, Béatrice; Minville, Vincent; et al.
Abstract : Objectives: Recovery from coma might critically depend on the structural and functional integrity of frontoparietal networks. We aimed to measure this integrity in traumatic brain injury and anoxo-ischemic (cardiac arrest) coma patients by using an original multimodal MRI protocol. Design: Prospective cohort study. Setting: Three Intensive Critical Care Units affiliated to the University in Toulouse (France). Patients: We longitudinally recruited 43 coma patients (Glasgow Coma Scale at the admission < 8; 29 cardiac arrest and 14 traumatic brain injury) and 34 age-matched healthy volunteers. Exclusion criteria were disorders of consciousness lasting more than 30 days and focal brain damage within the explored brain regions. Patient assessments were conducted at least 2 days (5 ± 2 d) after complete withdrawal of sedation. All patients were followed up (Coma Recovery Scale-Revised) 3 months after acute brain injury. Interventions: None. Measurements and Main Results: Functional and structural MRI data were recorded, and the analysis was targeted on the posteromedial cortex, the medial prefrontal cortex, and the cingulum. Univariate analyses and machine learning techniques were used to assess diagnostic and predictive values. Coma patients displayed significantly lower medial prefrontal cortex–posteromedial cortex functional connectivity (area under the curve, 0.94; 95% CI, 0.93–0.95). Cardiac arrest patients showed specific structural disturbances within posteromedial cortex. Significant cingulum architectural disturbances were observed in traumatic brain injury patients. The machine learning medial prefrontal cortex–posteromedial cortex multimodal classifier had a significant predictive value (area under the curve, 0.96; 95% CI, 0.95–0.97), best combination of subregions that discriminates a binary outcome based on Coma Recovery Scale-Revised). Conclusions: This exploratory study suggests that frontoparietal functional disconnections are specifically observed in coma and their structural counterpart provides information about brain injury mechanisms. Multimodal MRI biomarkers of frontoparietal disconnection predict 3-month outcome in our sample. These findings suggest that fronto-parietal disconnection might be particularly relevant for coma outcome prediction and could inspire innovative precision medicine approaches. Abstract : Supplemental Digital Content is available in the text.